Sustaining Business Amid Climate Change: Profit Drift and Investment Risks in Pelagic Fisheries - Wibowo, Martino; Mubarok, Faizul; Wardiwiyono, Sartini; Suntrayuth, Sid (Universitas Ahmad Dahlan, 2025)
This study examines the impact of climate change on the financial vulnerability and pelagic fisheries in Fisheries Management Area 711 investment risks, covering the ground fishing area of the Natuna Sea, the North Natuna Sea, and the Karimata Strait through direct survey. Data was collected from 100 fishermen using a quantitative approach and structural equation modeling (SEM) through a Likert-scale questionnaire to examine the interrelations among climatic factors, adaptive strategy, investment risk, and income. Findings demonstrate that storm frequency affects resource availability and investment risk, underscoring susceptibility to extreme weather phenomena. Investment risk functioned as a mediator, substantially influencing adaptive strategies and income. Adaptive solutions were identified to mitigate the adverse effects of investment risk on income by around 50 percent. Nonetheless, factors like sea level rise and sea temperature have shown no direct significant impact, indicating potential delayed or perceived consequences. The study underscores the importance of community-based adaptation measures to mitigate climate-induced economic vulnerabilities in fisheries, emphasizing the need for policymakers to enhance risk literacy among fishermen for improved socio-economic resilience.